(3GdbhGYO GdabgjIs - (3eMeO Hf HgGOQ Hf YHO Gddg GdRQcTj, CHh YHO Gddg, HOQ GdOjf , J (B794 (3g`s
(3ChdgG (B:s
(3CeG HYO aEf VHW GdCehQ GdefJTQI GdeJYOOI ai GdbhGfjf GdeJMOI gh ChYi dMaXgG hgPg bhGYO JVHW ddabjg CUhd GdePgH hQJHJgG Ydi MQha GdeYLe djSgd JfGhdgG s
(3BNQgG (B:s
(3hcGf HYV GdCTjGN jMci Cf GdTjN TeS GdOjf GdCUagGfi cGf jMaX eGFI fcJg ai GdLOd hcGf TjNg GdTjN GdCQehi jMaX Cda fcJg ai GdLOd hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1359s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs